2019
DOI: 10.1002/dta.2697
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of 29 synthetic cannabinoids and metabolites, amphetamines, and cannabinoids in human whole blood by liquid chromatography–tandem mass spectrometry – A New Zealand perspective of use in 2018

Abstract: We describe the validation of a method for the simultaneous analysis of 29 synthetic cannabinoids (SCs) and metabolites, 4 amphetamines, and 2 cannabinoids in human whole blood. This method enables one analysis to cover what previously required multiple analyses for these classic and novel drugs-of-abuse with diverse physicochemical properties. The scope of targeted analytes was based on the most prevalent drugs-ofabuse and SCs encountered at the New Zealand border in 2017 and included parent compounds and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…In the instance of 5F-ADB, multiple reports on the identification of M5 in blood have been published. [39][40][41][42]45,50 The authors only found one published report, by Kraemer et al, 43 mentioning the identification of M1 in blood and this did not provide detailed analysis of M1. The current report supplements this work, and provides the first detailed report on the presence of M1 in blood in the absence of the parent 5F-ADB compound.…”
Section: Identification Of Predominant Metabolites In Authentic Hummentioning
confidence: 99%
See 2 more Smart Citations
“…In the instance of 5F-ADB, multiple reports on the identification of M5 in blood have been published. [39][40][41][42]45,50 The authors only found one published report, by Kraemer et al, 43 mentioning the identification of M1 in blood and this did not provide detailed analysis of M1. The current report supplements this work, and provides the first detailed report on the presence of M1 in blood in the absence of the parent 5F-ADB compound.…”
Section: Identification Of Predominant Metabolites In Authentic Hummentioning
confidence: 99%
“…A number of toxicology reports from Bulgaria, Germany, Japan, New Zealand, Spain, Turkey, and the United States have included overdose, drowning, driving under the influence of drugs (DUID), and prison inmate fatalities linked to the consumption of 5F-ADB. 27,34,[39][40][41][42][43][44][45][46][47][48][49][50][51][52] Analysis of human biological specimens for the presence of synthetic cannabinoids typically entails identifying the parent drug in blood specimens, and/or its metabolites in urine. 7 However, this approach is incomplete, as many synthetic cannabinoid metabolites have been determined to be pharmacologically active and also appear in blood samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La littérature scientifique récente est très orientée « cannabinoïdes de synthèse », d'autant que certains ont été identifiés dans des e-liquides de vapotage [22]. Des méthodes existent dans le sang [23], les urines [24], la salive [25] et les cheveux [26]. Toutes ces méthodes mettent en avant plusieurs difficultés : connaître les nouveaux composés disponibles dans la rue et sur Internet, obtenir les substances de référence pour étalonner les instruments analytiques et surtout identifier correctement la molécule cible, du fait d'une métabolisation extensive.…”
Section: Perspectivesunclassified
“…To detect the use of NPS, metabolites and/or the parent molecule, is a particular analytical challenge in biofluids, being difficult because of the low concentrations encountered for the more potent substances and the lack of knowledge about many of them (15)(16)(17)(18)(19)(20). Table 2 shows the analytical conditions defined for each substance with the respective detection limits obtained.…”
Section: Limits Of Detectionmentioning
confidence: 99%